Advancing the Conceptualization and Operationalization of Novelty in Organizational Research - Rosenkopf, Lori; McGrath, Patia (Organization Science, 2011)
The construct of novelty is an important primitive for theories of organization learning, strategic change, and innovation. The organizational pursuit of novelty is generally theorized as necessary for long-term organizational adaptation and survival yet variance increasing in the short term. We argue that the recent explosion of studies of exploration and exploitation tend to conceptualize and operationalize novelty quite narrowly. In contrast, we treat novelty as a multidimensional construct and discuss implications of this approach for future research.